2006
DOI: 10.1099/jmm.0.46585-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid antibiotic sensitivity testing and trimethoprim-mediated filamentation of clinical isolates of the Enterobacteriaceae assayed on a novel porous culture support

Abstract: A porous inorganic material (Anopore) was employed as a microbial culture and microcolony imaging support. Rapid Anopore-based antibiotic sensitivity testing (AST) methods were developed to assess the growth of clinical isolates, with the primary focus on testing the response of the Enterobacteriaceae to trimethoprim, but with the method supporting a wider applicability in terms of strains and antibiotics. It was possible to detect the growth of Enterobacter aerogenes after 25 min culture and to distinguish a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…This might influence the specific growth rate of the cells, as it was shown that the growth rate of cells growing as surface colonies on a gelatin layer was smaller than the growth rate of cells in broth (6). The estimated doubling times of Escherichia coli 2613 and Enterobacter aerogenes grown on Anopore strips were, however, found to be comparable to the estimated doubling times in broth under nonstressing conditions (17,18).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…This might influence the specific growth rate of the cells, as it was shown that the growth rate of cells growing as surface colonies on a gelatin layer was smaller than the growth rate of cells in broth (6). The estimated doubling times of Escherichia coli 2613 and Enterobacter aerogenes grown on Anopore strips were, however, found to be comparable to the estimated doubling times in broth under nonstressing conditions (17,18).…”
mentioning
confidence: 77%
“…Anopore is a rigid aluminum oxide that is extremely porous (pore density is up to 50%) compared to other membranes (19). Recently, strips of Anopore were shown to be an effective support for culturing and imaging of microorganisms (17,18). Microbial growth is possible on Anopore strips when these are placed upon agar, which supplies the nutrients to the cells from beneath, through the pores.…”
mentioning
confidence: 99%
“…As with fluoroquinolone-induced filamentation, trimethoprim-induced filamentation occurs over a wide range of concentrations (0.06xMIC to 1xMIC), peaking at 0.13xMIC and decreasing thereafter [49]. The length of filaments generated by DNA disruptors and antifolates varies with duration of exposure, but is broadly similar in both cases [137], with cells capable of reaching over 50 µm [104,137]. Direct obstruction of Z-ring formation by SulA and other FtsZ inhibitors, like the indirect obstruction of Z-ring formation caused by DNA disruptors and antifolates, generates very long SOS-like filaments [138,139].…”
Section: Filamentationmentioning
confidence: 99%
“…The accuracy of pH papers was assessed against those of standards prepared from MRS medium (31) adjusted to the appropriate pH with HCl and measured using a PHM 82 pH meter (Radiometer, Denmark). For microcolony culture and imaging, sterile strips of PAO, sold as Anopore (20,21), were placed on the MRS-Gelrite or agar plates and inoculated with 10 4 to 10 6 CFU cm Ϫ2 of L. plantarum WCFS1. Strips were inoculated from a mid-logphase culture grown in MRS medium under anaerobic conditions.…”
Section: Methodsmentioning
confidence: 99%